(untitled) (Medico Legal Update, 2020)
A descriptive study to assess the knowledge, attitude and practice among postnatal mothers regarding postnatal exercise in selected village adopted by rural health centrepooncheri, Kanchipuram District, Tamil Nadu, India. The objectives are to assess the knowledge, practice and attitude among postnatal mothers regarding postnatal exercise in selected villages adopted by rural health centrepooncheri, Kanchipuram District, Tamil Nadu, India . To find out the association between level of knowledge, practice and attitude with demographic variables. The purposive sampling technique was used and the samples were 73. The data collection tools were validated and reability was established. The data were collected by self-administered questionnaire. The collected data tabulated and analyzed. Descriptive and inferential statistics were used. The study shows, In knowledge, 12.3% of the mothers had adequate knowledge, 52% of mothers had moderate knowledge and 35.6% of mothers had inadequate knowledge. In practice, 1.3% of mothers had adequate practice, 38.3% of mothers had moderate practice and 60.2% of mothers had inadequate practice, In attitude, 60.2% of mothers had negative attitude, 39.7% of mothers had undecided attitude and none of mothers had positive attitude among postnatal exercise.